Environmental Factors Involved in the High Incidence of Bladder Cancer in an Industrialized Area in North-Eastern Spain. (7th July 2022) - Caballero, José M.; Pérez-Márquez, Meritxell; Gili, José M.; Pereira, Juan C.; Gomáriz, Alba; Castillo, Carlos; Martín-Baranera, Montserrat
Abstract : Background . Bladder cancer (BC) is the most common of those affecting the urinary tract, and a significant proportion of the cases are attributable to tobacco use as well as occupational and environmental factors. Objective . The aim of this study is to estimate the current incidence of BC in an industrialized area in northeastern Spain and to analyze its time trends over three decades from an ecological perspective. Methods . Patients diagnosed with histologically confirmed primary BC, during 2018-2019, in an area in northeastern Spain (430, 883 inhabitants) were included. Crude and age-standardized incidence rates were estimated per 100, 000 person-years based on the number of individuals getting their first diagnosis. An exploratory time trend analysis was carried out to describe the evolution in tobacco use and occupational or environmental risk factors and the incidence of BC in the same area from the 1990s. Results . 295 patients were included (age 72.5 ± 10.3 years; 89.8% men). The crude rate was 62.6 (95% CI: 51.9–73.2) for men and 6.8 (95% CI: 3.4–10.3) for women. The annual rate adjusted to the European Standard Population was 85.3 (95% CI:75.0–95.5) for men and 7.0 (95% CI:4.5–9.5) for women. From 1994 to 2018, the prevalence of smokers decreased in men (42.3% to 30.9%) as well as in the active population working in the industry (44.36% to 22.59%). Nevertheless, the car fleet, especially diesel, has increased considerably. The annual mean concentrations of air (PM10, PM2.5, O3, and NO2 ) and water (nitrates, arsenic, trihalomethanes) pollutants were within the regulatory limit values, but not the maximum levels. Conclusions . The incidence of BC is one of the highest in men but not in women, despite the decrease in tobacco use and industrial activity (perhaps related to high latency after carcinogen exposure cessation) and despite the control of environmental pollution (the maximum regulatory limit probably needs to be lowered). Finally, a similar exposure to the carcinogen would result in a gender-specific differential incidence.